2019
DOI: 10.1016/j.ynstr.2019.100181
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular outcomes related to social defeat stress: New insights from resilient and susceptible rats

Abstract: Stress exposure is an important risk factor for psychiatric and cardiovascular disorders. Two phenotypes related to coping with stress can be observed in rodents that experience chronic social defeat stress (SDS): susceptible, showing social avoidance and behavioral changes related to depression, and resilient, showing none of these alterations. Moreover, a strong correlation exists between depression and the development of or mortality due to cardiovascular diseases. Nevertheless, little is known about cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 97 publications
5
21
1
Order By: Relevance
“…Nevertheless, the present findings are in line with previous evidence that rats identified as susceptible or resilient to SDS based on the latency to assume a submissive posture during a defeat episode did not show differences in corticosterone release during restraint stress exposure (Wood et al, 2010). Regarding our previous study (Morais-Silva et al, 2019), differences in the experimental timeline could explain the discrepancy between the two studies. In this study, we collected the plasma for corticosterone measurement 48 h after the cannulation surgery and compared it with 24 h in the previous study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Nevertheless, the present findings are in line with previous evidence that rats identified as susceptible or resilient to SDS based on the latency to assume a submissive posture during a defeat episode did not show differences in corticosterone release during restraint stress exposure (Wood et al, 2010). Regarding our previous study (Morais-Silva et al, 2019), differences in the experimental timeline could explain the discrepancy between the two studies. In this study, we collected the plasma for corticosterone measurement 48 h after the cannulation surgery and compared it with 24 h in the previous study.…”
Section: Discussionsupporting
confidence: 89%
“…(Isingrini et al, 2010). A recent study from our lab also showed that susceptible rats to SDS presented increased coat state deterioration (Morais-Silva et al, 2019).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…As such, we used the RI paradigm in Dsg2 mut/mut mice. The RI test has been extensively employed to study cardiac alterations in response to PSS in WT healthy rodents [39][40][41][42]. First, we show that despite the profound structural and functional cardiac alterations harbored, Dsg2 mut/mut mice behave and display anxiety levels similar to their WT counterparts when unstressed.…”
Section: Discussionmentioning
confidence: 80%